Ciguatera Toxins: Pharmacology, Toxicology, and Detection - Vetter, Irina; Zimmermann, Katharina; Lewis, Richard J. (CRC Press, 2014)
Ciguatera is the most Significant form of fish toxicoses in terms of the number and severity of poisoning episodes. The increased harvesting of tropical marine resources together with an increase in incidence has meant that fish consumption is associated with an increasing incidence of human intoxication, making ciguatera the most common nonbacterial seafood poisoning and a Significant health concern globally. Environmental degradation may play a role in the increased incidence of ciguatera, though the precise factors involved remain to be elucidated. Ciguatera differs from tetrodotoxin intoxication, one of the most lethal seafood toxins associated with the consumption of most puffer fish species. Ciguatera is becoming an increasingly global health concern with climate change and associated predicted increases in ocean temperatures causing a rise in the incidence of ciguatera. Epidemiological characterization of ciguatera has been limited by the lack of laboratory tests to conrm the presence of ciguatoxins, leaving diagnosis purely symptomatic based on detailed anamnesis.
CRIS-Team Scopus Importer:2025-03-24